PENGARUH SUSTAINABLE DEVELOPMENT GOALS TERHADAP PENGENTASAN KEMISKINAN DI PROVINSI BENGKULU DENGAN PKH SEBAGAI MODERATING - Maharani , Angelia; Arisandy , Yosy; Polindi , Miko (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2025)
This study aims to analyze influence of three pillars of sustainable development goals that are measured, namely Economic Pillar of Gross Regional Domestic Product (GRDP), Social Pillar of Human Development Index (HDI) and Environmental Pillar of Availability of Livable Housing (KRLH) on poverty alleviation in Bengkulu Province with the Family Hope Program as moderating. This study uses quantitative approach by collecting secondary data accessed from the official website of the Central Statistics Agency of Bengkulu Province. With sample data collection using a purposive sampling method totaling 50 samples. Data analysis uses Multiple Linear Regression and Moderated Regression Analysis (MRA) with the Eviews 12 application tool. The results in this study show that the GRDP variable has a significant positive effect on poverty, the HDI variable has negative but insignificant effect while KRLH variable has positive but insignificant effect and knowing that PKH is able to moderate effect of KRLH but is unable to moderate the effect of GRDP and HDI.